The Rhetoric of Space and Self in Racine's Bérénice. (December 2014) - Hammond, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> This essay explores the ways in which Racine defines the physical and conceptual spaces which his characters inhabit in Bérénice, and illustrates the semantic complexity of some of the play's principal terms.